Perceived Measures for Empowering Lodha Women in Odisha - Bhol, M; Mishra, M; Raj, R K; Mishra, J R (Indian Journal of Extension Education, 2020)
Lodha women have higher contribution for the maintenance of their family. Lodha Micro Project functioning inÂ Suliapada and Moroda blocks in Mayurbhanj district of Odisha has implemented various activities like farm production, income generation, infrastructure development, education, health and sanitation etc. for all round development of the Lodha community. The study to seek the suggestion of women regarding enhanced empowerment showed that participatory decision making and involvement in developing infrastructuresÂ benefitting majority, community approach, programming for all families, skill training, proper utilization of resources, liasoning for credit facilities, prioritization of income generating activities and beneficiary selection with common agreement were the important suggestions of the Lodha women for income generation leading to empowerment.